PECULIAR SIMILARITIES AND DIFFERENCES OF INCOMPLETE SENTENCES IN THE SPOKEN LANGUAGE OF FRENCH AND UZBEK - Tuyboeva Shakhnoza; G’aniyeva Madina (Bright Mind Publishing, 2025)
This article analyzes the similarities and differences in the expression of incomplete sentences in dialogic speech in French and Uzbek. The article first of all examines the concept of incomplete sentences and their role in speech. Further, the use of incomplete sentences in French and Uzbek, their structure, contextual features and communicative functions are analyzed. As similarities, the tendency to shorten and simplify information during communication in both languages is shown, and the grammatical structure, vocabulary and cultural context of the language are presented as differences.
Keywords: Incomplete sentence, dialogical speech, French, Uzbek language, similarities, differences, grammar, syntax, target speech, semantics.